Performing business risk assessment with real-world data set and data visualization. Issue 1 (1st May 2022) - Perdana, Arif; Tan, Janet
While real-world data may be publicly available and easily accessible, data require context to be delivered in a classroom. Apart from providing students experience working with real-world data for data analytics, this case also provides an example to university instructors on how to contextualize the real-world data set for teaching. This case equips students with relevant skills in data analytics that are aligned with the industry need. The context that we provided in this teaching case is applicable to undergraduate courses. We applied this case as one of business information system–related courses for the first-year university students.